APPLICATION OF INVENTORY GOODS IN COOPERATIVES EMPLOYEES PT. PLN (PERSERO) HEADQUARTERS WITH VISUAL BASIC 6.0 - Suhandriyanto Suhandriyanto; Don Elsafitra, SKom (Jurnal Sistem Informasi, 2005)
With existence of computerized system in process inventory at the official cooperation PT PLN (Persero) Head Office, particularly in the procurement of both goods inventory at the warehouse or the store, where the lack of functioning in inventory.It can be seen with him overcome the problems faced by both computerized and manual programs that can be seen in this writing and it takes a long time, since the process was done by computerized systems. Officers need to check goods store to ensure goods are requested exist or is empty, but enough to see the computer. Complaints from the unit as well as from members regarding the frequency of blank goods expected to be solved by the application procedures for inventory. In the return of damaged items or less are shipped from suppliers can be done quickly.